Slingshot [videorecording (Blu-Ray)] - Adams, R. Scott; Parker, Nathan C.; Affleck, Casey, 1975-; Fishburne, Laurence, III, 1961-; Beecham, Emily, 1984-; Morrissey, David (Decal, 2024)
Slingshot is a psychological thriller following an elite trio of astronauts aboard a years-long mission to Saturn's moon Titan. As they gear up for a dangerous slingshot maneuver, one astronaut struggles to maintain his grip on reality.